Construction of Dip-Coater - ADÁMEK, PETR (Journal of Education, Technology and Computer Science, 2016)
This paper describes construction of the “Dip-Coater”. The Dip-Coater serves to preparing of thin layers in liquid solutions. The instrument holds the microscope slide and dips it into active solution matter by defined velocity. The sample is dipped in the active solution matter for adjusted time and it is pulled out also with defined velocity. The developed and functionally approved system was primarily applied in experimental deposition of thin layers. The system offered the real opportunity of successful applications in scholar tasks in educational process. Subjects that can contribute to the development and construction of the system are the technology education of machinery the applied electronics and computer science. Another aim of the idea is the exploration of the existing or developed instruments and machines in educational process. The process should be realized by the interactive observation and researching of machines focused to their principles of function and their construction. Obtained theoretical knowledge and practical skills should be applied in construction of the other devices with the same or similar principles but with different purpose. The project also includes development of own electronic controlling and interface circuits and original software.